Content Analysis of the Movie "Who Killed Captain Alex" by Nabwana I.G.G - Mukhamad Kahfi Allutfi (Jurnal Ilmiah Komunikasi Makna, 2020)
The movie called "Who Killed Captain Alex" is a low-cost action movie produced by Uganda with English subtitles uploaded to the internet. This study aims to figure out the meanings and uses of symbols and visuals used in this movie. The theory in this study was Roland Barthes' Semiotics Theory with a critical paradigm. The subject of this study was the movie "Who Killed Captain Alex". The limitation of this study was denotation, connotation, and myth in the movie. The data collection techniques were done by collecting documentation data, observation data, and literature study. The data analysis focused on text, images, sounds and animation. The analysis process included: data reduction activities, data structuring, and data verification. The result of this study is that the movie "Who Killed Captain Alex" has various meanings denotatively, connotatively, and mythically. The limitation of this study was that it only focused on the pieces of the movie scenes. For further studies, it is suggested that researchers try looking for different fresh themes to study. Keywords: Internet, Media, Messages, Movie